Circular RNA CircMAP3K5 Acts as a MicroRNA-22-3p Sponge to Promote Resolution of Intimal Hyperplasia Via TET2-Mediated Smooth Muscle Cell Differentiation. Issue 4 (26th January 2021) - Zeng, Zhi; Xia, Luoxing; Fan, Shunyang; Zheng, Junmeng; Qin, Jinhong; Fan, Xuejiao; Liu, Yunfeng; Tao, Jun; Liu, Yingying; Li, Kang; Ling, Zhenwei; Bu, Yun; et al.
Abstract : Background: Aberrant expression of circular RNA contributes to human diseases. Circular RNAs regulate gene expression by sequestering specific microRNAs. In this study, we investigated whether circMAP3K5 (circular mitogen-activated protein kinase 5) could act as a competing endogenous microRNA-22-3p (miR-22-3p) sponge and regulate neointimal hyperplasia. Methods: Circular RNA profiling from genome-wide RNA sequencing data was compared between human coronary artery smooth muscle cells (SMCs) treated with or without platelet-derived growth factor. Expression levels of circMAP3K5 were assessed in human coronary arteries from autopsies on patients with dilated cardiomyopathy or coronary heart disease. The role of circMAP3K5 in intimal hyperplasia was further investigated in mice with adeno-associated virus 9–mediated circMAP3K5 transfection. SMC-specific Tet2 (ten-eleven translocation-2) knockout mice and global miR-22-3p knockout mice were used to delineate the mechanism by which circMAP3K5 attenuated neointimal hyperplasia using the femoral arterial wire injury model. Results: RNA sequencing demonstrated that treatment with platelet-derived growth factor–BB significantly reduced expression of circMAP3K5 in human coronary artery SMCs. Wire-injured mouse femoral arteries and diseased arteries from patients with coronary heart disease (where platelet-derived growth factor–BB is increased) confirmed in vivo downregulation of circMAP3K5 associated with injury and disease. Lentivirus-mediated overexpression of circMAP3K5 inhibited the proliferation of human coronary artery SMCs. In vivo adeno-associated virus 9–mediated transfection of circMap3k5 (mouse circular Map3k5) specifically inhibited SMC proliferation in the wire-injured mouse arteries, resulting in reduced neointima formation. Using a luciferase reporter assay and RNA pull-down, circMAP3K5 (human circular MAP3K5) was found to sequester miR-22-3p, which, in turn, inhibited the expression of TET2. Both in vitro and in vivo results demonstrate that the loss of miR-22-3p recapitulated the antiproliferative effect of circMap3k5 on vascular SMCs. In SMC-specific Tet2 knockout mice, loss of Tet2 abolished the circMap3k5-mediated antiproliferative effect on vascular SMCs. Conclusions: We identify circMAP3K5 as a master regulator of TET2-mediated vascular SMC differentiation. Targeting the circMAP3K5/miR-22-3p/TET2 axis may provide a potential therapeutic strategy for diseases associated with intimal hyperplasia, including restenosis and atherosclerosis. Abstract : Supplemental Digital Content is available in the text.